Activities of Provincial Medical Inspectors in Western Siberia in the Late XIX - Early XX Centuries - D. V. Andriyanova; D. Yu. Fedotova (Научный диалог)
The article is devoted to the study of medical practice in Western Siberia of the late XIX - early XX centuries. Attention is paid to the organization of medical practice in the Tobolsk province. The quantitative and official composition of medical personnel is described. The relevance of the study is due to the fact that on the basis of a wide body of diverse material for the first time the experience of the activities and biographies of medical inspectors: N. A. Stroganov, F. K. Zembitsky, V. I. Nikitenko, M. V. Miloslavsky, G. N. Egorov is considered. Their role in the development of medical practice in the Tobolsk province of 1895-1917 is described. It is shown that these inspectors had a high level of education and extensive experience in medical work. It is pointed out that, despite all the efforts and significant success in the development of medical practice, there were objective difficulties in this field of activity, among which there was a shortage of personnel, funding, long distances between settlements, the Russian-Japanese War and World War I, etc. The authors use a representative base of both published sources and unpublished materials from the collections of the State Archives of Tobolsk.